An efficient scheme for solving a system of time- fractional order differential-algebraic equations by using fractional Laplace iteration method - Hasan, Sameer; Namah, Eman (International Journal of Advanced Mathematical Sciences, 2016)
In this article, we propose an efficient algorithm for solving system of time- fractional differential-algebraic equations by using a fractional Laplace iteration method. The scheme is tested for some examples and the results demonstrate reliability and accuracy of this method.